DUKUNGAN SOSIAL TEMAN SEBAYA DAN MOTIVASI BELAJAR DENGAN SCHOOL WELL-BEING PADA SISWA SMP - Pertiwi, Rahma Sri; Hanoum, Magdalena; Purwantini, Lucky (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2024)
The study was conducted to determine the picture between peer social support and learning motivation with schoolwell-being at SMP Negeri 40 Bekasi City. This research method uses quantitative research with the variables studied, namely the relationship between peer social education (X1), and learning motivation (X2), towards school well-being (Y). This research was conducted at SMP Negeri 40 Bekasi City with the research subject of grade 8 students totaling 120 students, this research was conducted within a period of three months from January 16, 2023 to March 31, 2023. Data collection techniques in this study used observation, interviews and psychological measurement scales (questionnaires). The tests used in this study are descriptive tests, assumption tests, normality tests, linearity tests, correlation tests and multiple linear tests. Based on the research that has been done, it was found that there is a positive and significant relationship between peer social support and school well-being, and there is a positive and significant relationship between learning motivation and school well-being. There was an influence between peer social support and learning motivation with school well being positively and significantly with an R square value of 0.469 (46.9%) and an F Test Value of 15.962 with a significant level of p = 0.000 (ρ<0.05).